(untitled) - Đặng, Anh Đào (Hà Nội, 2010)
Hồi tưởng của tác giả về những chuyến đi
Keywords: Authors, Vietnamese,Tác gia Việt Nam,Vietnamese literature,Văn học Việt Nam; 20th century,Thế kỷ 20,20th century,Thế kỷ 20